2017
DOI: 10.1186/s12887-017-0853-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Helping Babies Breathe Quality Improvement Cycle (HBB-QIC) on retention of neonatal resuscitation skills six months after training in Nepal

Abstract: BackgroundEach year 700,000 infants die due to intrapartum-related complications. Implementation of Helping Babies Breathe (HBB)-a simplified neonatal resuscitation protocol in low-resource clinical settings has shown to reduce intrapartum stillbirths and first-day neonatal mortality. However, there is a lack of evidence on the effect of different HBB implementation strategies to improve and sustain the clinical competency of health workers on bag-and-mask ventilation. This study was conducted to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 31 publications
4
55
0
4
Order By: Relevance
“…Four articles were not included in the review even though they matched the inclusion criteria as they were covered in the above four studies. The Wrammert 2017 is covered in KC 2016 ; Ersdal 2013 , Mduma 2015 and Vossius 2014 are covered in Msemo 2013 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four articles were not included in the review even though they matched the inclusion criteria as they were covered in the above four studies. The Wrammert 2017 is covered in KC 2016 ; Ersdal 2013 , Mduma 2015 and Vossius 2014 are covered in Msemo 2013 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported improved perinatal outcomes at birth due to the implementation of the HBB programme . Several lessons have been learned from implementing the programme in health facilities and community settings .…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, Msemo et al 8 showed a 47% reduction in  24-hour early neonatal deaths (ENND) and 24% reduction in fresh stillbirths (FSB) following continued refresher HBB training (HBBT), while Goudar and colleagues showed a 46% reduction in FSB in India 9 10. In Nepal, Kc et al 11 observed a reduction in FSB and 24-hour ENND through repeated quality improvements cycles of HBBT, while Mduma et al 12 showed that frequent brief on-site HBBT was associated with a reduction in 24-hour ENND in a rural hospital in Tanzania. Incorporating early newborn care education into newborn resuscitation training was associated with reductions in 24-hour ENND in Zambia 13.…”
Section: Introductionmentioning
confidence: 99%
“…Among the effective practices identified, self-reflection by individual providers on each resuscitation performed is one of the simplest associated with positive change in outcomes. Monitoring and case review with weekly quality meetings can develop a culture of local data collection and use and help shift the narrative from punitive management practices to shared efforts toward more efficient and effective care [18, 19]. Debriefing, including use of video recordings, has been used in a variety of settings [18-22].…”
Section: Development Of Helping Babies Breathementioning
confidence: 99%
“…Monitoring and case review with weekly quality meetings can develop a culture of local data collection and use and help shift the narrative from punitive management practices to shared efforts toward more efficient and effective care [18, 19]. Debriefing, including use of video recordings, has been used in a variety of settings [18-22]. The transportability and generalizability of quality improvement approaches have been demonstrated in a cluster randomized trial among district hospitals in Nepal [23].…”
Section: Development Of Helping Babies Breathementioning
confidence: 99%